2006
DOI: 10.1309/dkcln4k2rk0v87yg
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-Cadherin and α-,β-,γ-Catenins in Patients With Bladder Cancer

Abstract: Loss of intercellular adhesion facilitates tumor invasion. To clarify the relation between altered expression of cell adhesion molecules and progression of T1 superficial bladder tumors, 101 cases (71 T1 tumors, 30 T2/T3 tumors) were examined immunohistochemically for E-cadherin and alpha-, beta-, and gamma-catenins. A highly significant correlation was observed between the decreased expression of all molecules and increased TNM stage (P < .001). Univariate analysis, performed in cases of T1 tumors, revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 34 publications
(34 reference statements)
4
3
0
Order By: Relevance
“…This was within the range previously reported in UCB patients (31–77 %) [8, 9] but lower than that reported in UTUC patients (68–71 %) [10, 11]. This could be due to our lower proportion of high stage tumors compared to the two other studies (50 vs. 54 and 61 %), as well as methodological differences in scoring, staining protocols, choice of antibody and/or antigen retrieval.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This was within the range previously reported in UCB patients (31–77 %) [8, 9] but lower than that reported in UTUC patients (68–71 %) [10, 11]. This could be due to our lower proportion of high stage tumors compared to the two other studies (50 vs. 54 and 61 %), as well as methodological differences in scoring, staining protocols, choice of antibody and/or antigen retrieval.…”
Section: Discussionsupporting
confidence: 92%
“…The role of E-cadherin expression as a prognostic factor in urothelial carcinoma was supported by previous studies mainly focusing on UCB [8, 9, 2427]. Our results confirm that decreased E-cadherin expression is indeed associated with a higher probability of disease recurrence and cancer-specific mortality in UTUC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, patients with TCC and SCC showed reduced E-cadherin expression in association with increased tumor grading, depth of invasion and LN metastasis. The TCC results are consistent with previous reports [31, 40, 41]. Similarly, current results are in line with that reported for SCC of non-bladder origin [42-46].…”
Section: Discussionsupporting
confidence: 93%